2012
DOI: 10.1002/ejlt.201100233
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CLA‐enriched TAG by Candida antarctica lipase under vacuum

Abstract: Conjugated linoleic acid (CLA)-enriched triacylglycerol (TAG) of 90 wt% was successfully synthesized in 10 h by direct esterification of glycerol and CLA using an immobilized lipase from Candida antarctica under vacuum. The best operating conditions for the synthesis of TAG were investigated according to the three parameters of temperature, enzyme loading, and vacuum. The synthesis of TAG increased with increasing temperature but it did not significantly change above 608C ( p>0.05). The increase of enzyme load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…d). The trend was similar to the effect of enzyme loading on esterification between conjugated linoleic acid and glycerol catalyzed by Novozym 435 under vacuum (Hong et al, ). It was observed that the reactants could not be well agitated when enzyme dosage exceeded 100% based on AKG if transesterification was carried out in a solvent‐free system.…”
Section: Resultssupporting
confidence: 79%
“…d). The trend was similar to the effect of enzyme loading on esterification between conjugated linoleic acid and glycerol catalyzed by Novozym 435 under vacuum (Hong et al, ). It was observed that the reactants could not be well agitated when enzyme dosage exceeded 100% based on AKG if transesterification was carried out in a solvent‐free system.…”
Section: Resultssupporting
confidence: 79%
“…LPC exists naturally on cell membranes as a minor component and has been widely used in the food, cosmetic, and pharmaceutical industries as emulsifier or medicine . LPC has been shown to be a preferred carrier form of FAs compared with triacylglycerols (TAG) and free FA, because it is more bioavailable than FAs in the TAG form and more stable and suitable for ingestion than FAs in the free FA form …”
Section: Introductionmentioning
confidence: 99%
“…However, we observed a different result in the present work that not only the TAG content but also the EE conversion was affected by the enzyme dosage: higher enzyme dosage led to higher EE conversion and TAG content. Hong et al (2012) also found an increase in the conversion of TAG when enzyme loading was increased from 5% to 10% throughout the course of esterification between conjugated linoleic acid and glycerol.…”
Section: Effect Of Substrate Ratios On Glycerolysismentioning
confidence: 70%